2007
DOI: 10.1016/j.jpainsymman.2006.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Deaths in Sweden: Are Individual Socioeconomic Factors Relevant?

Abstract: As the proportion of deaths in hospital falls, it is important to ensure that social disadvantage has no role in determining place of death. This study investigated the association between individual sociodemographic factors and deaths in hospitals for the population of Stockholm County, Sweden, using linked population registers. In 2002, 14,517 (87%) of the 16,617 adult decedents in Stockholm County had contact with health services in the three years before they died. Twenty-two percent (3,210) of these death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
(10 reference statements)
1
13
0
Order By: Relevance
“…This finding is consistent with studies in other publicly funded healthcare programs (Cartwright 1992;goddard and smith 2001;Hanratty et al 2007). Increased purchasing power for those in higher social positions has been linked to a demand for services (Coyte and Howell 2000).…”
Section: Income Effectsupporting
confidence: 92%
“…This finding is consistent with studies in other publicly funded healthcare programs (Cartwright 1992;goddard and smith 2001;Hanratty et al 2007). Increased purchasing power for those in higher social positions has been linked to a demand for services (Coyte and Howell 2000).…”
Section: Income Effectsupporting
confidence: 92%
“…Hanratty et al did not find any association between income and dying in hospital 29. We adjusted for other coherent variables to income, such as housing space and urbanicity, but still, income made a difference to the place of death.…”
Section: Discussionmentioning
confidence: 84%
“…In Sweden, individuals with a higher education are more likely to live in the community until the end of their lives, and they are more likely to be transferred to the hospital shortly before death than those with a primary education . Although another Swedish study found no association between hospital deaths and SES, the study population was limited to persons in Stockholm County who had at least one contact with the health system in the previous 3 years …”
Section: Discussionmentioning
confidence: 99%
“…38 Although another Swedish study found no association between hospital deaths and SES, the study population was limited to persons in Stockholm County who had at least one contact with the health system in the previous 3 years. 32 It is likely that the income measure partially captures the effect of education. People with higher education are more likely to live in cities or nearby where hospitals are available, and thus they can more easily be transferred to a hospital than their lower educated counterparts.…”
Section: Discussionmentioning
confidence: 99%